Respuesta :
Answer:
x₁ = -5/4 (-1.25)
x₂ = 3/2 (1.5)
Explanation:
8x² - 2x - 15 = 0
8x² + 10x - 12x - 15 = 0
2xx(4x + 5) - 12x - 15 = 0
2xx (4x + 5) - 3(4x + 5) = 0
(4x + 5) × (2x - 3) = 0
4x + 5 = 0 → x = -5/4 (-1.25)
2x - 3 = 0 → x = 3/2 (1.5)
Hope this helps! :)
Answer:Factor by grouping.
Hello!
_________________
8x^2-2x-15=0
( 4x + 5 ) (2x - 3) = 0
Explanation:
If any individual factor on the left side of the equation is equal to 0 , the entire expression will be equal to 0.
Set 4x + 5 equal to 0 and solve for x.
4x + 5 = 0
Subtract 5 from both sides of the equation.
4x = -5
Divide each term by 4 and simplify.
4x/4 = -5/4
x = -5/4
Set 2x - 3 equal to 0 and solve for x.
x = 3/2
The final solution is all the values that make ( 4x + 5) ( 2x -3) = 0 true.
x = - 5/4 , 3/2.
Hope this helped you and sorry for take so long!